2019
DOI: 10.1042/bsr20182144
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acid sphingomyelinase activity ameliorates endothelial dysfunction in db/db mice

Abstract: Acid sphingomyelinase (aSMase) plays an important role in endothelial dysfunction. Here, we show that elevated aSMase activity and ceramide content were reduced by desipramine treatment in diabetic animals. The inhibitor of aSMase, desipramine, improved vascular dysfunction in db/db mice. High glucose (HG)-induced up-regulation of aSMase activity and ceramide levels were restored by treatment with aSMase siRNA or desipramine in endothelial cells. In addition, aSMase siRNA or desipramine treatment increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…Prior studies of obese rodents revealed that ceramide inhibition could improve obesity-related metabolic abnormalities such as insulin resistance, hyperglycemia, and hyperlipidemia (9, 19, 2123). Prior studies also revealed that blunting de novo ceramide synthesis could ameliorate hepatic steatosis in obese animals (6, 11).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of obese rodents revealed that ceramide inhibition could improve obesity-related metabolic abnormalities such as insulin resistance, hyperglycemia, and hyperlipidemia (9, 19, 2123). Prior studies also revealed that blunting de novo ceramide synthesis could ameliorate hepatic steatosis in obese animals (6, 11).…”
Section: Discussionmentioning
confidence: 99%
“…ASM also plays a major role in the development of many other disorders such as cardiovascular and metabolic diseases. Its downregulation was reported to alleviate vascular endothelial insulin resistance in diabetic rats [152] and improve vascular dysfunction in diabetic mice [153]. Amitriptyline inhibits nonalcoholic steatohepatitis and atherosclerosis as induced by high-fat diet and lipopolysaccharide in mice [154].…”
Section: Assays For Studies Of Asm Inhibitorsmentioning
confidence: 99%
“…Leptin can induce vasodilatation through the Ob-Rb/STAT3/Akt signal pathways [ 57 ], and endothelial leptin resistance impairs eNOS activation and reduces endothelium-dependent vasodilation [ 58 ]. Moreover, the ASM/ceramide pathway mediates vascular dysfunction by regulating the Akt/eNOS/NO signaling pathway, and the inhibition of the ASM/ceramide pathway can improve endothelium-dependent vasodilation [ 59 , 60 ]. Here, the levels of serum eNOS and NO in HFD-fed rats were normalized by AMI and IMI.…”
Section: Discussionmentioning
confidence: 99%